Oxalá Cresçam Pitangas (2005/7) e É Dreda ser Angolano (2006/8) : Olhares sobre Luanda através do cinema de retomada angolano e do cinema de poeira - Costa, Renata Dariva (2020)
This research is inserted, contextually, in the complex movement of the construction of Angolan national identity, in Luanda, from the analysis from the film Oxalá Cresçam Pitangas, Histórias de Luanda (2005/7) and É Dreda ser Angolano (2006/8). The first documentary is directed by Ondjaki and Kiluanje Liberdade and is a Portuguese-Angolan production that is part of the Angolan retake cinema (2003), which emerged from the end of the Post-election War (1992-2002), with the death of Jonas Malheiro Savimbi, founder of the National Union for the Total Independence of Angola (UNITA). In addition to UNITA, other movements and parties linked to the decolonization and independence of Angola will be seen, as well as some impasses in cinema about Angola. The second film, É Dreda Ser Angolano (2006/8), it is a collective production by Fazuma and is linked to the dust cinema of Angola, that is, to the cinema made in Angolan mussekes, peripheral regions of Angola. These two “ways” of making and thinking about cinema in Angola, reflect on the relationship between Cinema-History and as narratives of national identities.